Trends and Predictors of Readmission among Coronary Artery Disease Patients in a Community Heart Hospital in Nepal - Dhungel, Sachin; Samir Gautam; Bishal KC; Mazhar Khan; Rajesh Panjiyar; Abhishesh Shakya; Manisha Yadav; Prayatna Bhattarai; Dhawal, Laxmi; Subash Baral (Journal of National Heart and Lung Society Nepal, 2023)
Background: Patients of Coronary artery disease after index hospitalization gets readmitted to the same or different hospital for cardiac or noncardiac causes. The objective of this study if to find the trends of readmission pattern and different factors determining readmission . Methods: The study is retrospective hospital based study for one year. Eligible patients were patients having documentation of coronary artery disease and readmission in time frame of one year in 2079 BS. Results: Out of 749 admitted patient with coronary artery disease, 143 (19%) patients were readmitted. Mean age was 63.3 ± 13.4. There were 88 (61.5%) male and 55(38.5%) female. Readmission rate for 30 days was 2.9% and 1 year 11.2%. Forty (38%) of readmitted patients had been admitted more than one time. Common presentations were chest pain 60 (42%), shortness of breath 42(29.4%), fever 11 (7.7%), epigastric pain 9 (6.3%), hemiparesis 8(5.6%), dizziness 4 (2.8%), hematemesis 2(1.4%) and hempoptysis 2 (1.4%). Top factors determining readmission were enlisted were presence of wall motion abnormalities 96(67.1%), anemia 83 (58%), diagnostic invasive procedure in past 80 (55.9%), hypertension 76(52.4%), low systolic function 75 (52.4%), angina 60(43%), diabetes 59(41.3%), heart failure 50 (35%), revascularization( PCI) 50 (35%), infarction 39(27.3 ), COPD 32(22.4%), infections 29(20.3%),acute kidney injury 25 (17.5), hypothyroidism 16(11.2%), dyslipidemia 15(10.5), CKD 14(9.8), CVA 13(9.1), APD 12 (8.4), arrhythmia 10 (7%) h/o CABG, 10 (7%) and UGI bleeding 10 (7%). Conclusion: Readmission forms nineteen percentage of total admissions and readmission rate calculated within 30 days of admission as 2.9%.